2015
DOI: 10.1186/s40064-015-1234-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary formic acid and astaxanthin on the survival and growth of Pacific white shrimp (Litopenaeus vannamei) and their resistance to Vibrio parahaemolyticus

Abstract: A 90-day feeding trial was conducted to evaluate the effects of formic acid (FA) and astaxanthin (AX) on growth, survival, immune parameters, and tolerance to Vibrio infection in Pacific white shrimp. The study was divided into two experiments. In experiment 1, postlarvae-12 were randomly distributed into six groups and then fed four times daily with six experimental diets contained 0.3 % FA, 0.6 % FA, 50 ppm AX, 0.3 % FA + 50 ppm AX, 0.6 % FA + 50 ppm AX, or none of these supplements (control diet). After 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 41 publications
5
58
0
Order By: Relevance
“…, ; Chuchird et al . ). Total viable bacterial and Vibrio counts in the hepatopancreas of marine shrimp were found to be lower when fed diets with 20 g kg −1 OAB compared to the control treatment without any organic acids (Ng et al .…”
Section: Mode Of Action and Effects Of Dietary Organic Acidsmentioning
confidence: 97%
See 2 more Smart Citations
“…, ; Chuchird et al . ). Total viable bacterial and Vibrio counts in the hepatopancreas of marine shrimp were found to be lower when fed diets with 20 g kg −1 OAB compared to the control treatment without any organic acids (Ng et al .…”
Section: Mode Of Action and Effects Of Dietary Organic Acidsmentioning
confidence: 97%
“…It was reported that white shrimp fed diets with a combination of formic acid and astaxanthin was no better than using singly or in combination in terms of preventing V. parahemolyticus infections (Chuchird et al . ). Despite the contradictory reports to date on the synergistic effects of organic acids and other functional feed additives, recent trends indicate that organic acids manufacturers are combining organic acids with additives such as essential oils, enzymes and plant/herbal extracts for potentially stronger antimicrobial and health‐promoting effects on aquatic animals.…”
Section: Strategies To Enhance Efficacy Of Organic Acids In Aquafeedsmentioning
confidence: 97%
See 1 more Smart Citation
“…As growth was not influence, it would appear that the increased consumption we observed could be and artefact of reduced stability. Similarly, other studies reported that added formic acid or organic acid not only did not affect the growth performance, but also improved survival rate after the challenge test (Chuchird, Rorkwiree, & Rairat, ; Defoirdt, Halet, Sorgeloos, Bossier, & Verstraete, ; Koh, Romano, Zahrah, & Ng, ) and feed utilization (Koh et al, ). Those study results indicated that pH is not the main factor in influencing the performance in high silage diet.…”
Section: Discussionmentioning
confidence: 70%
“…Carotenoids can also improve survival rate, enhance resistance to several stress conditions as well as pigmentation. Therefore, both organic acids and carotenoids have the potential to be used in catfish farming as feed additives [1].…”
Section: Introductionmentioning
confidence: 99%